HOIL-1L interacting protein (HOIP) as an NF-kappaB regulating component of the CD40 signaling complex. - Bruce S Hostager; Daniel K Fox; Douglas Whitten; Curtis G Wilkerson; Betty A Eipper; Victor P Francone; Paul B Rothman; John D Colgan (PLoS ONE, 2010)
The tumor necrosis factor receptor (TNFR) superfamily mediates signals critical for regulation of the immune system. One family member, CD40, is important for the efficient activation of antibody-producing B cells and other antigen-presenting cells. The molecules and mechanisms that mediate CD40 signaling are only partially characterized. Proteins known to interact with the cytoplasmic domain of CD40 include members of the TNF receptor-associated factor (TRAF) family, which regulate signaling and serve as links to other signaling molecules. To identify additional proteins important for CD40 signaling, we used a combined stimulation/immunoprecipitation procedure to isolate CD40 signaling complexes from B cells and characterized the associated proteins by mass spectrometry. In addition to known CD40-interacting proteins, we detected SMAC/DIABLO, HTRA2/Omi, and HOIP/RNF31/PAUL/ZIBRA. We found that these previously unknown CD40-interacting partners were recruited in a TRAF2-dependent manner. HOIP is a ubiquitin ligase capable of mediating NF-kappaB activation through the ubiquitin-dependent activation of IKKgamma. We found that a mutant HOIP molecule engineered to lack ubiquitin ligase activity inhibited the CD40-mediated activation of NF-kappaB. Together, our results demonstrate a powerful approach for the identification of signaling molecules associated with cell surface receptors and indicate an important role for the ubiquitin ligase activity of HOIP in proximal CD40 signaling.